The Effectiveness of Using BBC News Video to Enhance Students’ Speaking Pronunciation and Fluency - Iksan, Muhammad Verill; Salam, Urai; Rezeki, Yanti Sri (PROJECT (Professional Journal of English Education), 2025)
This research explored the effectiveness of incorporating BBC News videos to enhance the speaking pronunciation and fluency of Islamic High School students. Using a pre-experimental design, the research assessed students' speaking abilities before and after exposure to BBC News. Statistical analysis revealed a significant enhancement in the students' speaking skills. The findings showed that the use of BBC News videos contributed to a noticeable, moderate enhancement in their pronunciation and fluency. This research highlights the potential of BBC News as a meaningful and engaging tool for enhancing students' speaking abilities, emphasizing its value in language learning.